2021
DOI: 10.3390/ani11072078
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Major Pasture-Borne Parasitoses (Gastrointestinal Nematodes, Liver Flukes and Lungworms) in German Dairy Cattle Herds, Association with Management Factors and Impact on Production Parameters

Abstract: Pasture-borne parasites adversely affect bovine health and productivity worldwide. In Europe, gastrointestinal nematodes, especially Ostertagia ostertagi, the liver fluke Fasciola hepatica and the lungworm Dictyocaulus viviparus represent the most important parasites of dairy cattle. The present study assessed exposure towards these parasites among 646 cattle herds in three parts of Germany during 2017–2019 via antibody detection in bulk tank milk (BTM). Overall, O. ostertagi levels indicative of production lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Although seroprevalence values are difficult to compare with the prevalence determined in our investigation, as the sensitivity differs and only patent infections can be detected by coproscopy [ 13 , 35 ], the most recent seroprevalence study confirms higher exposure to liver flukes in the south than in the north of Germany [ 28 ]. However, F. hepatica BTM seroprevalence in the region “East” was only 1% [ 28 ] compared to nearly 8% patent infections in our study. This may be explained by different sample sets (BTM samples were collected in 2017–2019, faecal samples in 2018–2020, and participating farms overlapped only partially), but needs to be clarified in future studies.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although seroprevalence values are difficult to compare with the prevalence determined in our investigation, as the sensitivity differs and only patent infections can be detected by coproscopy [ 13 , 35 ], the most recent seroprevalence study confirms higher exposure to liver flukes in the south than in the north of Germany [ 28 ]. However, F. hepatica BTM seroprevalence in the region “East” was only 1% [ 28 ] compared to nearly 8% patent infections in our study. This may be explained by different sample sets (BTM samples were collected in 2017–2019, faecal samples in 2018–2020, and participating farms overlapped only partially), but needs to be clarified in future studies.…”
Section: Discussionmentioning
confidence: 96%
“…In a bulk tank milk (BTM) study conducted in 2008, seroprevalences amounted to 9-19% in the German federal states included in the region "West" [27], but this region was not included in a recent BTM study on fasciolosis in Germany examining samples from 2017 to 2019 [28]. Although seroprevalence values are difficult to compare with the prevalence determined in our investigation, as the sensitivity differs and only patent infections can be detected by coproscopy [13,35], the most recent seroprevalence study confirms higher exposure to liver flukes in the south than in the north of Germany [28]. However, F. hepatica BTM seroprevalence in the region "East" was only 1% [28] compared to nearly 8% patent infections in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ostertagi antibody status and milk production and quality parameters [ 51 53 ]. Interestingly, in their recent study which in large parts was based on the data set collected in the underlying three years cross–sectional study throughout Germany, Springer et al [ 22 ] identified a negative impact on milk production level only in high–performance dairy breeds while lower milk fat content was observed in dual–purpose herds positive for O . ostertagi .…”
Section: Discussionmentioning
confidence: 99%
“…ostertagi on farm level was assessed by BTM antibodies determined with the IDEXX Fasciolosis Verification Test (IDEXX GmbH) and the Svanovir O . ostertagi –Ab ELISA (Boehringer Ingelheim) in a previous study [ 22 ]. As in the previous study and in accordance with the manufacturer’s recommendation, F .…”
Section: Methodsmentioning
confidence: 99%